MAKNA KEDAULATAN TUHAN DALAM PANGGILAN MENJADI HAMBA TUHAN BERDASARKAN YEREMIA 1:5-10 - Living Jovieli Hia; Harefa, Yaaro (Misioner, 2023)
The call to become a servant of God is a statement of God's sovereignty in each person's life according to His will, but there are people who respond to God's call by bringing up their various reasons or limitations to reject the call, therefore this article proposes that the call is declared. based on God's sovereignty. In this study the authors used exegesis and literature methods, which means collecting references that support the discussion from books of journal articles that are in the same direction as the discussion. This research is designed to contribute to people who struggle about their calling.